The EUTHANASIA DAN BUNUH DIRI : The Euthanasia dan bunuh diri - Fadila Anastasya; Shifa Aliya Putri; Della Nurfadilah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Euthanasia and suicide are issues closely related to humanitarian, moral, legal, and religious values. Euthanasia refers to the intentional act of ending a person’s life in order to relieve suffering caused by severe or incurable illness. Meanwhile, suicide is the act of taking one’s own life due to various factors, such as psychological pressure, depression, social problems, or economic difficulties. Both issues often become subjects of debate because they concern human rights and ethical boundaries in life. The factors underlying euthanasia generally include prolonged pain, medical conditions with little chance of recovery, and the desire to end a patient’s suffering. On the other hand, suicide may be triggered by mental disorders, feelings of hopelessness, family conflicts, environmental pressures, and the loss of life motivation. The purpose of euthanasia is commonly associated with reducing the patient’s suffering, while suicide is more related to an individual’s inability to cope with life’s pressures. From an Islamic perspective, human life is considered a gift and a trust from Allah SWT that must be protected and respected. Therefore, Islam prohibits active euthanasia and suicide because both are regarded as intentional acts of taking human life. Islam teaches its followers to remain patient, strive for solutions, and draw closer to Allah when facing illness or hardships in life. Thus, problems should not be solved by ending life, but through effort, prayer, and support from surrounding people